"A Genius without Direction": The Abortive Exile of Dugmore Boetie and the Fate of Southern African Refugees in a Decolonizing Africa. Issue 2 (13th July 2021) - Lawrance, Benjamin N.; Kumalo, Vusumuzi R.
Abstract: The flight of South African writer Dugmore Boetie from his home in the Sophiatown neighborhood of Johannesburg to Dar es Salaam, Tanganyika, in mid- to late 1960 highlights the fuzzy distinction between exile and refuge before international refugee protections extended to Africa. Like many decolonial refugees after the Sharpeville Massacre, Boetie fled political persecution, lured abroad by the possibility of resettlement in London under the United Kingdom's open-door policy to British Commonwealth citizens. Unlike many contemporaries, however, Boetie had yet to attain literary fame and had few notable advocates. Fragmentary exilic archives shift attention away from refugee reception and toward motives for flight, speaking to the ad hoc strategies of escape and survival characteristic of the transitional decolonization epoch. While networks of anticolonial, anti-apartheid sympathizers generally welcomed the first waves of exiles, politically connected socioeconomic elites were best positioned to make dangerous journeys. Men and women from all over Africa sought refuge in the 1950s and 1960s before global anti-apartheid activism was fully formed, but political subjectivities, legal statuses, and shifting citizenship statutes impeded or expedited individual paths. The better connected entered the United Kingdom, the United States, or the Soviet Union for education or employment. Those bereft of connections were forced to make a difficult choice between returning home or becoming another humanitarian statistic.